Spatial Analysis of the Impact of Nickel Mining on Vegetation Cover Change in Obi Island, Indonesia - Heinrich Rakuasa; Vadim V Khromykh; Ahmad Rifai; Philia Christi Latue (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
The nickel mining activities in Indonesia, particularly on Obi Island, have significantly altered land-use patterns, marked by an expansion of bare land due to topsoil and vegetation removal. This has led to a drastic decline in dense and productive vegetation cover, which previously served as a carbon sink and habitat for local biodiversity. Utilizing Landsat 8 Surface Reflectance Collection 2 Tier 1 imagery (2015, 2020, 2025), this study employed the Normalized Difference Vegetation Index (NDVI) within the Google Earth Engine and ArcGIS Pro platforms to assess spatiotemporal changes in vegetation cover. Results indicate a substantial increase in non-vegetated areas and a significant reduction in moderate-to-high-density vegetation, particularly within the mining core zone, directly attributable to nickel extraction activities, which drive habitat fragmentation and ecosystem degradation. Although rehabilitation and revegetation efforts demonstrate localized success, ongoing mining pressures pose risks of further environmental damage without sustainable management. This study underscores the critical need for stringent environmental regulations and targets ecological restoration to mitigate mining impacts and ensure the long-term sustainability of Obi Island's ecosystems